2016
DOI: 10.1038/srep37040
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of upright standing in adults with late-onset Pompe disease

Abstract: Pompe disease is a rare disorder producing muscle weakness and progressive impairments in performing daily motor activities, such as walking and standing. Most studies have focused on dysfunctions at cellular level, restricting the examination of gross motor functions to qualitative or subjective rating scales evaluations. With the aim of providing an instrumented quantification of upright standing in Pompe disease, we used a force platform to measure the center of pressure over three foot positions and with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 44 publications
3
16
0
Order By: Relevance
“…Increasing of temporal and spatial complexity reflects the need to integrate many information for the coordination and optimization of the postural performance. This interpretation is shared with most of the relevant literature 28 , 29 , 44 49 .…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Increasing of temporal and spatial complexity reflects the need to integrate many information for the coordination and optimization of the postural performance. This interpretation is shared with most of the relevant literature 28 , 29 , 44 49 .…”
Section: Discussionsupporting
confidence: 53%
“…For example, the loss of ability to produce adaptive and complex motor pattern in many postural disorders is associated with a decrease in ApEn 29 , 45 , 49 , while increases in ApEn are reported when postural training is adopted to improve sensory and/or motor coordination in several contexts 28 , 47 , 48 , 50 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also clearly indicated that greater instability along the AP direction than the ML direction during quiet standing (1.62 > 1.05 and 0.52 > 0.42). This is consistent with literature and it is commonly understood that the passive mechanical constraints at ankle and knee joints largely minimizes the ML motion, while more degrees of freedom are available for the movements along the AP direction [27]. …”
Section: Discussionsupporting
confidence: 91%
“…Additionally, analysis of these features might be a tool for following up on future therapeutic strategies (i.e., next level ERT order gene therapy) [9]. There is a paucity in this research, with one study reporting reduced spatio-temporal parameters during gait in 22 LOPD patients on ERT [10] and another showing deficits in standing postural stability among five LOPD patients [11].…”
Section: Introductionmentioning
confidence: 99%